2023
DOI: 10.3390/molecules28196970
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, Spectral Characterization and Antifungal Activity of Novel Phenolic Acid Triazole Derivatives

Pan-Lei Xiao,
Xiu-Ying Song,
Xin-Ting Xiong
et al.

Abstract: At present, phenolic acid derivatives and triazole derivatives have a good antifungal effect, which has attracted widespread attention. A series of novel phenolic acid triazole derivatives were synthesized, and their structures were characterized by IR, MS, NMR, and X-ray crystal diffraction. Compound methyl 4-(2-bromoethoxy)benzoate, methyl 4-(2-(1H-1,2,4-triazol-1-yl) ethoxy)benzoate, 4-(2-(1H-1,2,4-triazol-1-yl)ethoxy)benzoic acid and 4-(2-(1H-1,2,4-triazol-1-yl) ethoxy)-3-methoxybenzoic acid crystallize in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The interaction between 1,3-dimethylsemithioglycoluril 4 a and DEAD (1.2 equiv.) was chosen for studying as a model reaction (EtOH, reflux, 2 h, similar to the preparation of imidazo [4,5e]thiazolo [2,3-c] [1,2,4]triazines, [17,18] Scheme 1. There are two potential pathways for annulation to heterocycles with thiourea moiety using DEAD: thiazole or thiazine rings formation.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between 1,3-dimethylsemithioglycoluril 4 a and DEAD (1.2 equiv.) was chosen for studying as a model reaction (EtOH, reflux, 2 h, similar to the preparation of imidazo [4,5e]thiazolo [2,3-c] [1,2,4]triazines, [17,18] Scheme 1. There are two potential pathways for annulation to heterocycles with thiourea moiety using DEAD: thiazole or thiazine rings formation.…”
Section: Synthesismentioning
confidence: 99%
“…Plant infectious diseases severely decrease the yield of crops as well as their quality, leading to more than $220 billion losses annually in the global economy. [1][2][3][4][5][6] Worldwide analysis has shown that pathogenic fungi are one of the most common causes of these diseases, accounting for approximately 30 % of all cases. [6,7] The use of fungicides is an effective method for combating fungal diseases, but the widespread use of known chemical fungicides can lead to drug resistance in fungi, highlighting the need for the development of new scaffolds.…”
Section: Introductionmentioning
confidence: 99%